AVALIAÇÃO PADRONIZADA DE PACIENTES COM DPOC NO MOMENTO DA ALTA HOSPITALAR STANDARDIZED ASSESSMENT OF COPD PATIENTS AT THE TIME OF HOSPITAL DISCHARGE - Letícia de Araújo Morais; Marcus Barreto Conde; Marcelo Fouad Rabahi (UniEVANGÉLICA, 2017)
Objective: To translate, culturally adapt the hospital discharge checklist proposed by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) and develop a form that allows a standardized assessment of important items at hospital discharge of patients with Chronic Obstructive Pulmonary Disease (COPD). Methods: A methodological study performed in patients at the time of hospital discharge after decompensation for Chronic Obstructive Pulmonary Disease (COPD) in three hospitals in the city of Goiânia. The translation and cultural adaptation of the checklist proposed by GOLD was carried out, containing seven items to be evaluated at the time of hospital discharge for two pulmonologists, then the retranslation of the same by English-speaking professional and then created a final version in Portuguese. To assess the reproducibility and responsiveness of the document created, the same was applied in ten patients by two researchers. The kappa coefficient for statistical analysis of reliability was used. Results: After the translation and cultural adaptation of the discharge checklist proposed by GOLD, a standardized form was prepared for measuring all seven items in the checklist. The kappa coefficient is equal to 1 for all seven items of the document. Conclusion: The standardized form for evaluating the items of the hospital discharge checklist proposed by GOLD was reproducible, reliable and fast to use, and can be used by a multidisciplinary team at discharge from patients hospitalized for COPD, thus allowing a standardized verification of Essential for the best management of these patients.